A Father, What for? In connection with the show “Lettre au père” of Jean-Yves Ruf, according to the text of Franz Kafka "Dearest Father" - Wormser, Gérard; Lahire, Bernard; Castelain-Meunier, Christine (Sens public)

(untitled) (Département des littératures de langue française, 2014)
Can the young man of today visualize the impossible dialogue of Kafka with his father? The evolution of the society has questioned the father's long time role of supervision and authority. However, does that not open up a restructuring of his figure? The depth of the father's influence is far-reaching. The English paediatrician and psychoanalyst Donald W. Winnicott said, “He can become a maternal substitute for infants, providing child care from the ages of birth to two years as is maternity care”. Paternal love and everyday father/child relationship has a critical role in the development of early childhood. However, is this structuring enough? Does this not open up an era lacking references? Today, what is the father's place at a time of contemporary changes in family life?